Implementation of Customer Relationship Management, Service Quality, and Its Influence on Community Satisfaction through Grievance Handling Facilities in East Java Customs Area - Maduwinarti, Ayun; Taali , Muhammad; Prihatinta, Triana (International Journal of Social and Management Studies, 2024)
Advances in digital technology and various regulatory changes have triggered a spike in trade in imported products domestically which are sold cheaply, and in the last two years it has increased rapidly. This had an impact on the buildup in the inspection process at the Customs office, so that there were several products that experienced delays in delivery and became a problem for consumers and traders who resold these imported products domestically. This study aims to examine the work performance of the East Java customs office in handling consumer complaints, by applying the customer relationship management approach and service quality standards as stipulated in PAN-RB Ministerial Decree No. 14 of 2017 concerning community satisfaction with the performance of government officials in public services. This study took purposive sampling of consumers in East Java with the aim of testing the consumer relations management approach, and the quality of customs services moderated by complaint handling on customer satisfaction. The results of multiple regression analysis prove that customer relationship management (CRM) and quality of customs services together have a direct effect on customer satisfaction; customer relationship management, and the quality of customs services together influence customer satisfaction which is moderated by complaint handling; and partially the application of CRM and quality of service through handling complaints has an effect on community satisfaction. This is also evidenced by the value of the customer satisfaction index which shows that consumers are satisfied with the services of the customs office in East Java.